2023
DOI: 10.3390/ijms241311045
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Transcriptional Analyses Provide Insight into Maintaining Ion Homeostasis of Sweet Sorghum under Salt Stress

Huan Guo,
Chun-Ya Nie,
Zhen Li
et al.

Abstract: Sweet sorghum is an important bioenergy grass and valuable forage with a strong adaptability to saline environments. However, little is known about the mechanisms of sweet sorghum coping with ion toxicity under salt stresses. Here, we first evaluated the salt tolerance of a sweet sorghum cultivar “Lvjuren” and determined its ion accumulation traits under NaCl treatments; then, we explored key genes involved in Na+, Cl−, K+ and NO3− transport using transcriptome profiling and the qRT-PCR method. The results sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In light of this, rigorous validation of candidate associations is a non-negotiable requirement [55] before one can proceed with more downstream applications. It is as part of this corroboration endeavor that Zhao et al [34], Ma et al [35], and Guo et al [36] envisioned their works, using alfalfa (Medicago sativa), Phoebe bournei (a widely conserved tree in China because of its economic and ecological value), and sorghum (Sorghum bicolor) as study organisms for multiple abiotic stresses, such as salt (all three species), drought (the former two taxa), and heat (the second species). Performing integrated assessment of multiple stresses such as these also enables long-standing questions concerning the scale of molecular pleiotropism beneath concomitant abiotic stresses to be addressed [56], a matter which has already been approached in this Special Issue by Wirojsirasak et al [33] in a multi-environment framework [12], but has yet to be addressed in a multi-trait setup [57].…”
Section: Polygenic Diversity For Abiotic Stress Tolerancementioning
confidence: 75%
See 2 more Smart Citations
“…In light of this, rigorous validation of candidate associations is a non-negotiable requirement [55] before one can proceed with more downstream applications. It is as part of this corroboration endeavor that Zhao et al [34], Ma et al [35], and Guo et al [36] envisioned their works, using alfalfa (Medicago sativa), Phoebe bournei (a widely conserved tree in China because of its economic and ecological value), and sorghum (Sorghum bicolor) as study organisms for multiple abiotic stresses, such as salt (all three species), drought (the former two taxa), and heat (the second species). Performing integrated assessment of multiple stresses such as these also enables long-standing questions concerning the scale of molecular pleiotropism beneath concomitant abiotic stresses to be addressed [56], a matter which has already been approached in this Special Issue by Wirojsirasak et al [33] in a multi-environment framework [12], but has yet to be addressed in a multi-trait setup [57].…”
Section: Polygenic Diversity For Abiotic Stress Tolerancementioning
confidence: 75%
“…In terms of candidate gene functional validation [62], Guo et al [36] also corroborated our knowledge on the genomic architecture for key abiotic stresses by performing transcriptome profiling and qRT-PCR for salt tolerance in sorghum. Ultimately, research investigating how sorghum reacts to salt stress sheds essential light on the plant's extraordinary capacity to adapt to harsh conditions [63].…”
Section: Pleiotropism Underlying Concerted Responses To Abiotic Stressesmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition to the ability of T. ciferrii WLW to produce MA while tolerating high salt, the underlying molecular mechanism of the response to salt stress also attracted our attention. A series of studies related to the mechanism of salt tolerance have shown that membrane proteins, ion homeostasis, and transcription factors (TFs) are closely related to the strong salt tolerance of microorganisms under high-salt conditions [ 31 , 32 , 33 ]. Therefore, we used transcriptomic techniques to explore the reason for survival despite high-salt conditions from multiple perspectives, including the expression of key genes in terms of membrane proteins, ionic homeostasis, and salt-stress-related transcription factors.…”
Section: Resultsmentioning
confidence: 99%
“…Globally, soil salinization poses a major threat to plant growth and productivity [1]. Affecting more than 1 billion hectares of land [2], the lack of freshwater resources and unreasonable irrigation methods have aggravated salinization [3] and brought huge economic losses to irrigated areas [4].…”
Section: Introductionmentioning
confidence: 99%